Agroindustrial Study of Banana Crackers and Salai Based on Income, Value Added and Break Even Point - Lukman Hidayat; Hidayat Koto; Odi Andanu (Badan Penerbitan Fakultas Pertanian (BPFP), 2018)
The aim of this research was to analyze and calculates the income, added-value, and break even point of agroindustry that processing bananas into banana crackers and salai. Methods of data collection in this research were using observation and interviews. Data were analyzed using descriptive analysis, qualitative and quantitative, for the value-added, income, Break Even Point (BEP) and Revenue Cost ratio (R/C). The results shown that the average of value added per kilograms for Salai Rp. 4.371,37, sweet and salted banana crackers are Rp 2.944,00 and Rp 3.627,90. The income of salai, sweet and salted banana crackers per year’s are Rp. 29.566.251,-, Rp. 18.437.067, 96,- and Rp. 20.286.567,-. The average of BEP per month’s for salai is salai Rp. 1.415.636, sweet and salted banana crackers are Rp. 988.966, and Rp.781.352. The Average of BEP, units or packs per month’s for salai is 145 packs, sweet banana crackers were 124 packs and salted were 98 packs. R/C of Salai was 1.66, sweet banana crackers were 1.49 and salted was 1.71. Added-value of banana Salai Rp. 743, 47 more than salted banana crackers, amounted to 1.471,37 compared to sweet banana crackers. Banana salai income greater Rp. 9.279.684 than salted banana crackers, amounting to Rp. 11.129.183 compared to sweet banana crackers.Keywords: Value Added, Income, Banana crackers, Salai, Break Even Point